2024
DOI: 10.1186/s13049-024-01181-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of orthopaedic injuries after the kahramanmaraş earthquake: a retrospective study from a hospital located in the affected region

Murat Gök,
Mehmet Ali Melik

Abstract: Background The purpose of this retrospective, single-institutional study was to report the clinical features and outcomes of orthopaedic injuries after the Kahramanmaraş earthquake. Methods An institutional database review was conducted to evaluate the results of patients who applied to our hospital’s emergency department after the Kahramanmaraş earthquake. Trauma patients referred to orthopaedics and traumatology were identified. Patient records w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…They concluded that most injuries requiring treatment after earthquakes (87%) were orthopedic in nature 6 . Gök et al also reported 112 patients (42.2%) among 265 patients who were admitted to the emergency department and referred to the orthopedics and traumatology departments within the rst week following the Kahramanmaraş earthquake 7 . In their study, 68 orthopedic patients underwent surgery, including 22 cases who underwent operations performed on the rst day after the earthquake, whereas 25 cases operations were performed on the second day.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that most injuries requiring treatment after earthquakes (87%) were orthopedic in nature 6 . Gök et al also reported 112 patients (42.2%) among 265 patients who were admitted to the emergency department and referred to the orthopedics and traumatology departments within the rst week following the Kahramanmaraş earthquake 7 . In their study, 68 orthopedic patients underwent surgery, including 22 cases who underwent operations performed on the rst day after the earthquake, whereas 25 cases operations were performed on the second day.…”
Section: Discussionmentioning
confidence: 99%